2014
DOI: 10.1161/circinterventions.113.000512
|View full text |Cite
|
Sign up to set email alerts
|

Administration of a Loading Dose Has No Additive Effect on Platelet Aggregation During the Switch From Ongoing Clopidogrel Treatment to Ticagrelor in Patients With Acute Coronary Syndrome

Abstract: Background— Ticagrelor outperforms clopidogrel in preventing cardiovascular events in acute coronary syndrome. Despite the inclusion of a loading dose in the Platelet Inhibition and Patient Outcomes (PLATO) trial for all patients randomized to ticagrelor, it may not be necessary in patients receiving ongoing clopidogrel therapy. The aim of the present study was to assess whether a ticagrelor loading dose is associated with a further platelet inhibition during the switch from clopidogrel to ticagrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Platelet aggregation is also significantly reduced 2 h after the first administration of ticagrelor [10]. So hs-cTnT was chosen at 2 h after PCI as a parameter to reflect whether a loading dose of ticagrelor could decrease post-PCI myocardial necrosis in stable CAD patients already receiving clopidogrel therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Platelet aggregation is also significantly reduced 2 h after the first administration of ticagrelor [10]. So hs-cTnT was chosen at 2 h after PCI as a parameter to reflect whether a loading dose of ticagrelor could decrease post-PCI myocardial necrosis in stable CAD patients already receiving clopidogrel therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the PLATelet inhibition and patient Outcomes (PLATO) trial, reversible long-term P2Y12 inhibition with ticagrelor was better than that with clopidogrel for the prevention of cardiovascular and total death, myocardial infarction (MI), and stent thrombosis, without an increase in the rates of major bleeding in a broad population of patients with ACS, who began treatment upon hospital admission [7,8]. Although a loading dose of ticagrelor was used in PLATO trial [9], a recent study demonstrated that a loading dose of ticagrelor was not associated with a further platelet inhibition after switching from clopidogrel to ticagrelor for patients with ACS receiving ongoing clopidogrel treatment [10]. However, the above study only included clopidogrel responders [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Many other studies exploring the pharmacodynamic profiles of switching from clopidogrel to prasugrel or ticagrelor have been conducted (Tables II and III in the online-only Data Supplement). 18,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] All studies have consistently shown enhanced platelet inhibition when escalating from clopidogrel to prasugrel or ticagrelor, regardless of clinical setting, as well as a reduction in rates of high on-treatment platelet reactivity (HPR), 18,48-70 a well-defined marker of risk of ischemic recurrences, including stent thrombosis. 10,11 These effects are achieved more promptly after administration of an LD compared with an MD regimen.…”
Section: Escalation (Switching From Clopidogrel To Prasugrel or Ticagmentioning
confidence: 99%
“…2 The novel antiplatelet agent, ticagrelor, has several advantages over the long-standing clopidogrel, as the virtual absence of nonresponders and the more powerful platelet inhibition. As highlighted by Gurbel et al, 1 clopidogrel nonresponders were excluded from our study, for multiple reasons.…”
mentioning
confidence: 99%